Experiencias del proceso de implementación de reforma institucional de cuatro gobiernos regionales del Perú 2007-2010 - Coronel Salirrosas, Jesús (2013)
In this research work it was developed and implemented a plan for institutional reform to four regional governments of Peru (Cajamarca, Junín, La Libertad and San Martín) during the period of time 2007-2010. An institutional assessment was performed for each of the four regional governments collecting data on governance (institutional development plans, annual operating plan, investment plan, budget, institutional reform plan, regional ordinances, etc.) directly and through surveys and interviews. Direct contact was made with each of the Institutional Reform Commissions (CRI) to determine the objectives and strategies for the reform. Based on the results of the diagnosis it was prepared an institutional reform plan containing objectives and strategies organized into two main guiding principles of reform: institutional modernization and management by programs. Proposals for measurements of the reform were developed that are put to consideration of rulers and ruled people. The diagnosis revealed that the main weaknesses of governance of regional governments were: bureaucratic management approach, lack of coordination between state agents, absence of a results-based management approach, weak institutional capacity, inefficient systems and processes, a leafy regulations that slow processes, organizational structure disjointed and bureaucratic unmotivated and without obligation employees. The partial implementation of the institutional reform gave rise to: managerial reforms, strengthening concerted strategic planning, strengthening public investment management, sectoral organizational reforms, joint regional action in the provinces, substantial increase in the budget execution capacity.